AN ANALYSIS OF DEVELOPMENT ICT IN LEARNING ENVIRONMENT ON ESP CLASSROOM - Ida Maulida (Media Bina Ilmiah, 2023)
In the English for Specific Purposes (ESP) method of language education that needs of the learner are given priority. The purpose of ESP is to increase the relevance of English language instruction to student requirements. ESP is a specific educational technique to accomplish this. This research focuses on specific subjects of the English for Business Study Program aiming to equip students with the knowledge and skills to succeed in the ESP class. Based on the results and qualitative analysis of 30 participants in the study who obtained the ESP program to learn English by using qualitative descriptive. Furthermore, this research uses descriptive qualitative method analysis by presenting data through questionnaire and observations. The study investigates how students respond about the use of technology in the classroom. In this case, it will provide useful subjects and activities that will enable students to learn more and improve their English for educational purposes. The study findings represent that student was extremely positive assessments of the use of Information and Communication Technology (ICT) in English teaching learning, and their participation in the ESP learning environment. It provided tremendous topics and activities which make both teachers and students enrich their knowledge and develop their English skills in educational purposes.